International Security : A Very Short Introduction - Browning, Christopher S. (Oxford Oxford University Press, 2013)
Since the end of the Cold War, the international security agenda has become increasingly important. This book considers traditional topics such as war and peace, military strategy and nuclear weapons, alongside other issues such as climate change international migration, poverty, and international terrorism.
Include Illustrations, References and Index.
A Very Short Introduction.
Keywords: Security, International -- International relations--Philosophy -- Power (Social sciences) -- Terrorism--Prevention